Estudo Fitoquímico de Byrsonima gardneriana A. Juss (Malpighiaceae) - Rolim, Thaísa Leite (2009)
The family Malpighiaceae is predominantly found in tropical and subtropical areas and comprises about 75 genera and 1,300 species. The Byrsonima genus has about 150 species and is mainly found in Mexico, spreading across South America. According to the bibliographic research on Byrsonima gardneriana A. Juss there are no studies about chemical constituents and pharmacological studies are rare. This work describes the isolation and structural identification of some chemical constituents of the stem bark of Byrsonima gardneriana A. Juss, with the objective of increasing the chemical knowledge on the genus Byrsonima, as well as on the family Malpighiaceae. The phytochemical study of the chloroform phase of B. gardneriana resulted in the isolation of five triterpenes: 3β- hydroxiolean-12-ene, first reported in the species, 3-oxo-5-ene-glutinone and friedoolean-14- en-3-one, first described in the genus, friedelan-3-one and lup-20(29)-en-3-ol both first reported in the species. The chemical constituents were identified by analysis of data obtained by spectroscopic methods such as Infrared, 1H and 13C Nuclear Magnetic Resonance, with the aid of two-dimensional techniques, besides comparison with literature data.